2020
DOI: 10.1002/mgg3.1125
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1/miR‐185‐5p/IGF2 axis regulates the invasion and migration of colon cancer

Abstract: Background Long noncoding RNAs (lncRNA) are important in the growth and metastasis of colon cancer. The objective of this study was to describe the potential role of lncRNA NEAT1 in the progression of colon cancer. Methods Quantitative real‐time polymerase chain reaction was used for detecting NEAT1, miR‐185‐5p, and IGF2 in colon cancer cells and tissues. The potential diagnostic value of NEAT1 in colon cancer was analyzed with the receiver operating characteristic curve. Kaplan–Meier method was applied for ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In addition, lncRNA nuclear-enriched abundant transcript 1 (NEAT1) is newly discovered and has been localized in cell nuclear paraspeckles. Increasing evidence has revealed that NEAT1 is upregulated in multiple cancers and facilitates cell invasion and migration by being a sponge for miRNAs [137][138][139][140]. Recently, NEAT1 has been proven to be highly expressed in multiple myeloma, and knockdown of NEAT1 inhibited the invasion and metastasis of myeloma cells.…”
Section: Invasion and Metastasismentioning
confidence: 99%
“…In addition, lncRNA nuclear-enriched abundant transcript 1 (NEAT1) is newly discovered and has been localized in cell nuclear paraspeckles. Increasing evidence has revealed that NEAT1 is upregulated in multiple cancers and facilitates cell invasion and migration by being a sponge for miRNAs [137][138][139][140]. Recently, NEAT1 has been proven to be highly expressed in multiple myeloma, and knockdown of NEAT1 inhibited the invasion and metastasis of myeloma cells.…”
Section: Invasion and Metastasismentioning
confidence: 99%
“…LncRNA NEAT1, a scaffold factor, has been investigated to take part in diverse cancer progression. Zhuang et al (2020) indicated NEAT1 was up-regulated in colon cancer and its overexpression promoted the metastasis of colon cancer cells. NEAT1 was indicated to be overexpressed in pancreatic cancer and increased cell proliferation and metastases in pancreatic cancer cells (Feng et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Hsa-miR-184 seems to be a suppressive miRNA in some tumors like glioma and nasopharyngeal carcinoma [ 31 , 32 ], but it is overexpressed in adrenocortical carcinoma and renal carcinoma, where the expression level is stepwise growing along with tumor stage. Hsa-miR-185-5p enhances proliferation of pituitary cells [ 30 ], but it inhibits invasion and migration of colon cancer and hepatocellular carcinoma [ 33 , 34 ]. Hsa-miR-181a-2-3p was reported as overexpressed in head and neck cancer and adenoid cystic carcinoma [ 35 , 36 ], while it is downregulated in papillary thyroid carcinoma [ 37 ].…”
Section: Discussionmentioning
confidence: 99%